Survei Minat Belajar Siswa Terhadap Pembelajaran Penjas Secara Daring Pada Masa Pandemi Covid-19 di SMAN 1 Telagasari - Apif Fathurrohman; Akhmad Dimyati; Abdul Salam Hidayat (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine student interest in learning physical education online during the covid-19 pandemic at SMAN 1 Telagasari. This research is a quantitative descriptive research, the method used in this research is a survey using random sampling technique. The population in this study were all students of class XI SMAN 1 Telagasari totaling 388 students. The instrument used is a questionnaire, the analytical technique used is to pour the frequency into a percentage. Based on the results of this study, students' interest in learning physical education online during the Covid-19 period at SMAN 1 Telagasari was in the "Medium" category with the highest frequency in the medium category 42 students 52.50%. Students' interest in learning physical education online during the covid-19 period at SMAN 1 Telagasari was categorized as very high 6 students or 7.50%, high 12 students or 15.00%, moderate 42 students or 52.50%, low 14 students or 17.50%, very low 6 students or 7.50%.